E07 Progressive Iron Accumulation In Huntington Disease Basal Ganglia: A Longitudinal Study - Sánchez-Castañeda, C; Hagberg, G; Squitieri, F; Sabatini, U (Journal of neurology, neurosurgery and psychiatry, 2014)
Background There is neuropathological evidence of iron accumulation in basal ganglia associated with the striatal volume loss in Huntington disease (HD). T2*-weighted imaging is a useful measure to study iron distribution in the brain since magnetic susceptibility maps correlate with chemically-determined iron concentration. Increased iron levels in the caudate, putamen and globus pallidus have been shown in HD patients and presymptomatic subjects. However, none study to date has approached the longitudinal progression of iron content in basal ganglia in the different clinical stages. Aims To longitudinally explore the iron abnormalities in basal ganglia in HD clinical subgroups. Methods Forty-two CAG mutation carriers underwent T2* relaxometry (multiecho EPI sequence) and 3D T1-weighted imaging (MDEFT sequence) twice on a 3T Siemens scanner. Subjects were classified as: 13 presymptomatic subjects (PreHD; UHDRS motor score <5) and 29 symptomatic subjects (HD). We analysed caudate, putamen and globus pallidus volumes and their mean iron content at baseline and after 16,46 ± 5 months follow-up. Image processing was performed combining FSL 4.1.9 and Freesurfer 5.2. Age and time between scans were introduced as covariates. Results Considering all subjects together, we found a significant progressive volume decrease in the caudate (p = 0.04) and putamen (0.01) nuclei. Iron content increased with time in all three nuclei, showing statistical significance in putamen (0.05) and globus pallidus (0.04). When considering the clinical subgroups, PreHD subjects have deeper caudate volume loss (p = 0.009) and iron increase in the putamen (p = 0.04); while HD patients had more putamen volume loss (p = 0.01). Conclusions Our study shows that iron content progressively accumulates in basal ganglia during HD progression. The relation of iron content accumulation to grey matter loss and neurodegeneration needs further analysis. Abstract E07 Table 1 Demographic and clinical characteristics of the sample